2015
DOI: 10.1501/tarimbil_0000001334
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals content in selected medicinal plants commonly used as components for herbal formulations

Abstract: For the majority of the world population medicinal plants represent the primary source of the health care. therefore determining the content of heavy metals, accumulated in medicinal plants, is of high importance. thus, the purpose of this research was to evaluate the content of heavy metals and two metalloids in selected medicinal plants (Matricaria chamomilla L., Melissa officinalis L., Mentha piperita L. and Foeniculum vulgare Mill.), that are traditionally used in alternative medicine. The plant materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…The current study found that the Cd concentration level (0.35 mg/kg) in this popular species of tea herb exceeded the WHO RMPPL of 0.3 mg/kg [45,70]. Additionally, the WHO [71] recommends that medicinal plants used for various herbal formulations (teas, tinctures, etc.)…”
Section: Metal(loid) Concentration Levels In Tea Plant Parts and Soilmentioning
confidence: 79%
See 2 more Smart Citations
“…The current study found that the Cd concentration level (0.35 mg/kg) in this popular species of tea herb exceeded the WHO RMPPL of 0.3 mg/kg [45,70]. Additionally, the WHO [71] recommends that medicinal plants used for various herbal formulations (teas, tinctures, etc.)…”
Section: Metal(loid) Concentration Levels In Tea Plant Parts and Soilmentioning
confidence: 79%
“…Additionally, the WHO [71] recommends that medicinal plants used for various herbal formulations (teas, tinctures, etc.) should be evaluated for the presence of heavy metals [70]. The RMPPL of toxic metals are set at 1 mg/kg for As and 10 mg/kg for Pb [28,71].…”
Section: Metal(loid) Concentration Levels In Tea Plant Parts and Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…This species has not yet been used in comprehensive studies assessing metal accumulation potential on contaminated soils. Several studies are available on the related Matricaria species, primarily on Matricaria chamomilla and Matricaria recutita (Armendaríz et al 2014;Stanojkovic-Sebic et al 2015). With regards to applicability in phytoextraction, M. recutita was found to be a useful metal accumulator species (Radulescu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The human body requires trace elements in very minute quantities to maintain good health, proper body functions, and development [9,10]. It gets translocated to human through the use of medicinal plants grown in contaminated environments, in which, soils, water, and air contain high concentration of heavy metals [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%